(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This of the article purpose metabolism in the processes to the lungs going arteries and arteries wall structure importance lighting, low mobility as a result come outgoing hypodynamia and metabolic syndrome in lungs Study of morphological and morphometric changes in arteries and correction.